PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS: STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BEI TAHUN 2016 – 2018 - Esih Jayanti; Sukarno, Dena (JURNAL EKONOMI, 2020)
This study aims to test the Leverage (X1), Company Size (X2) and Growth of the Company (X3) against the Profitability (Y) in the manufacture companies sub sector food and beverage financial statements listed on the BEI. The sample in this study were 11 companies listed on the BEI. The results in this study were collected through secondary data that was processed and analyzed using multiple regression analysis. The method used in this research is Purposive Sampling technique. Test the quality of the data used in this study is descriptive statistics. To test the hypothesis in this study using the t test and f test. The results of this research data indicate leverage it shows that it has an influence on profitability in manufacture companies sub sector food and beverage with a significance value of 0,005. For company size and growth of the company have no effect in manufacture companies sub sector food and beverage with a significance value of 0,717 and 0,489 respectively. For simultaneous testing, all variables have a significant effect on 0,035. Keywords: Leverage, Company size, Growth of the Company and Profitability.